2019
DOI: 10.4149/neo_2018_180414n238
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOST2 enhances proliferation and metastasis in gastric cancer

Abstract: This study investigates the influence of long noncoding RNA HOST2 on the biological functions of gastric cancer cells; including proliferation, migration and invasion. Differentially expressed lncRNAs in gastric cancer (GC) were screened by microarray analysis, and HOST2 expression in GC tissues and cell lines was determined by quantitative real-time PCR (qRT-PCR). GC cell proliferation, migration and invasion were detected by CCK-8, wound healing and transwell assays. Western blot investigated expression of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Liu D reported HOST2 was highly expressed in glioma tissues and its down-regulation could inhibit the growth and invasion of glioma cells [28]. Similar results were reported in hepatocellular carcinoma [24,25], cervical cancer [26], and gastric cancer [27]. In breast cancer, function of HOST2 in MCF-7 cell (Lumina A type breast cancer cell) was reported [33].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Liu D reported HOST2 was highly expressed in glioma tissues and its down-regulation could inhibit the growth and invasion of glioma cells [28]. Similar results were reported in hepatocellular carcinoma [24,25], cervical cancer [26], and gastric cancer [27]. In breast cancer, function of HOST2 in MCF-7 cell (Lumina A type breast cancer cell) was reported [33].…”
Section: Discussionmentioning
confidence: 54%
“…In 2015, HOST2 was firstly reported in human ovarian cancer which is highly expressed, and function as an oncogene in epithelial ovarian cancer cells by binding to miRNA let-7b [23]. In hepatocellular carcinoma [24,25], cervical cancer [26], gastric cancer [27] and glioma [28], HOST2 was also up-regulated and played a oncogene role in tumourigenesis and development. However, there is still lack of exact mechanisms about how HOST2 experts its functions in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…HOST2 is a newly discovered lncRNA, and it was originally found in ovarian cancer [16] and exerted proliferative effects and migration facilitation in ovarian cancer [17]. However, accumulating evidence proposes that HOST2 also plays a part in other cancer cells, such as hepatocellular carcinoma [28], breast cancer [29,30], pancreatic cancer [31], HPV-positive cervical cancer [32] and gastric cancer [33]. Therefore, the functions of HOST2 in cancer cells deserve further research.…”
Section: Discussionmentioning
confidence: 99%
“…a number of studies have demonstrated that lncrnas serve a regulatory role in Gc as oncogenes or tumor suppressor genes (8,9). For example, lncRNA human ovarian cancer specific transcript 2 has been reported to accelerate cell proliferation and metastasis in Gc (10). in addition, Pan et al (11) observed that lncrna differentiation antagonizing non-protein coding rna promoted Gc cell proliferation and invasion by activating spalt-like transcription factor 4. in recent years, lncrna ViM antisense rna 1 (ViM-aS1) has been reported to promote cell migration and invasion through regulating the epithelial-mesenchymal transition (eMT) in colorectal cancer and preeclampsia (12,13).…”
Section: Introductionmentioning
confidence: 99%